PENGARUH MEDIA GAME EDUKATIF QUIZ TERHADAP HASIL DAN MINAT BELAJAR SISWA PADA MATERI BANGUN DATAR KELAS III SEKOLAH DASAR KABUPATEN TULUNGAGUNG - cahyani, Tiara; Ana, Ria Fajrin Rizqy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effect of educational quiz game media on students’ learning outcomes and learning interest in plane geometry material for third-grade elementary school students in Tulungagung Regency. A quantitative approach with a pre-experimental method and a One Group Pretest-Posttest Design was employed in this study. The sample consisted of 15 third-grade students of SDN 1 Karangtalun selected using total sampling. Data were collected through learning outcome tests, learning interest questionnaires, and interviews as supporting data. Data analysis was conducted using descriptive and inferential statistics through multivariate normality testing and Multivariate Analysis of Variance. The findings revealed that the use of educational quiz game media had a significant effect on students’ learning outcomes and learning interest. Learning activities supported by game-based media created a more interactive and enjoyable learning environment, which encouraged students’ active participation during the learning process. The improvement in learning outcomes and learning interest indicates that educational quiz game media can serve as an effective alternative to support mathematics learning on plane geometry material in elementary schools.